Can Twilight Become a Natural Therapy? An Examination of the Interpretation of QS. An-Nur Verse 35 from a Psychological Perspective - Aminaturroisah, Faza; Atiq, Dewi Shinta Baitul (QiST: Journal of Quran and Tafseer Studies, 2026)
This article examines the relationship between the twilight phenomenon and mental health through an interpretative study of the Qur’an, particularly Surah An-Nur verse 35. The research employs a qualitative descriptive method using a library research approach, analyzing classical and contemporary tafsir to understand the symbolism of light (nūr) as a representation of divine guidance and spiritual illumination. The interpretative process highlights key metaphors in the versesuch as the niche (mishkāt), the lamp (miṣbāḥ), and the radiant lightinterpreted as symbols of inner clarity and faith. The exegetical findings are then correlated with scientific studies on the biological and psychological effects of twilight exposure. Biologically, evening light contributes to serotonin production and the regulation of circadian rhythms, which support emotional stability and reduce anxiety. Psychologically, contemplation of twilight fosters reflective awareness, gratitude, and inner calm. The structure of the discussion covers three main aspects: the interpretation of light symbolism in the verse, the biological mechanisms of light exposure, and its psychological implications for mental health. The study concludes that viewing twilight as a reflection of divine beauty can also function as a form of natural therapy that nurtures inner peace and mental well-being.